2018
DOI: 10.3758/s13415-018-00667-y
|View full text |Cite
|
Sign up to set email alerts
|

Using emotion regulation strategies after sleep deprivation: ERP and behavioral findings

Abstract: Sleep deprivation is suggested to impact emotion regulation, but few studies have directly examined it. This study investigated the influence of sleep deprivation on three commonly used emotion regulation strategies (distraction, reappraisal, suppression) in Gross's (1998) process model of emotion regulation. Young healthy adults were randomly assigned to a sleep deprivation group (SD; n = 26, 13 males, age = 20.0 ± 1.7) or a sleep control group (SC; n = 25, 13 males, age = 20.2 ± 1.7). Following 24-h sleep de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 69 publications
0
29
1
Order By: Relevance
“…Hence, most participants likely did succeed to downregulate experienced unpleasantness when instructed to do so. Contrary to our hypothesis and findings in previous studies (24,29,36), sleep deprivation caused no significant decrease in ability to reappraise.…”
Section: Emotion Regulation Through Reappraisalcontrasting
confidence: 99%
See 3 more Smart Citations
“…Hence, most participants likely did succeed to downregulate experienced unpleasantness when instructed to do so. Contrary to our hypothesis and findings in previous studies (24,29,36), sleep deprivation caused no significant decrease in ability to reappraise.…”
Section: Emotion Regulation Through Reappraisalcontrasting
confidence: 99%
“…Negativity bias is that sleep deprivation causes neutral stimuli to be perceived as more negative, making the emotional baseline and starting point for reappraisal not fully comparable with that of the full-sleep condition (24). Negativity bias can partially explain differences in study results, since Tamm (24,29,36). In this study and in the study by Shermohammed et al (37), behavioral results were based on ratings of a negative emotion only.…”
Section: Emotion Regulation Through Reappraisalmentioning
confidence: 75%
See 2 more Smart Citations
“…A study investigating the impact of cognitive reappraisal on early emotion processing found that whilst a more positive P200 was elicited when cognitive reappraisal was implemented to enhance a negative emotional response, no P200 modulation was observed when the instructions were to reduce the negative response (Wu et al, 2013). This suggests that the adaptive regulatory effects of cognitive reappraisal may only have an impact on later evaluative stages of emotional processing.…”
mentioning
confidence: 99%